Trends in Neisseria Gonorrheae Antimicrobial Susceptibility in California, 2005–2016. (4th October 2017) - Stoltey, Juliet; Han, Emily; Burghardt, Nicole; Chow, Joan; Bauer, Heidi
Abstract: Background: Resistant Neisseria gonorrheae (NG) is a growing concern in California, nationally, and globally. Since 1987, California has participated in the Gonococcal Isolate Surveillance Project (GISP), a Centers for Disease Control and Prevention-funded project to monitor trends in antimicrobial susceptibility in sentinel STD clinic sites throughout the United States. We sought to describe trends in California NG susceptibility to ceftriaxone (CRO) and azithromycin (AZI), recommended therapy for NG, for 2005–2016. Methods: Per GISP protocol, cultures are collected from the first 25 men presenting with NG urethritis each month at GISP clinic sites in California, and antimicrobial susceptibility testing (AST) is performed via agar dilution at GISP regional laboratories. Reduced susceptibility (RS) to CRO was defined as minimum inhibitory concentration (MIC) ≥0.125 µg/ml and AZI MIC ≥2 µg/ml. Demographics and MIC trends over time were examined. Results: Between 2005 and 2016, there were 9, 692 NG isolates submitted in California GISP clinics. There were 24 (0.25%) isolates with RS to CRO and 92 (0.96%) isolates with RS to AZI. There was a higher proportion of isolates from men who have sex with men with RS to AZI (but not CRO) compared with men who have sex with women (chi-squared P -values: AZI = 0.0015; CRO = 0.70). In 2016, the percent of isolates demonstrating RS to AZI increased to 3.69% ( n = 32), compared with 0.69% of isolates with RS to AZI in 2005–2015 (chi-squared P -value < .0001); there was no significant difference in the percent of isolates with RS to CRO in 2016 compared with prior years (Figure 1). Figures 2 and 3 demonstrate the distribution of AZI MICs and CRO MICs, respectively, from 2005–2016. There have been no isolates to date in California GISP with RS to both ceftriaxone and azithromycin. Conclusion: Gonococcal surveillance data demonstrate an increase in the proportion of isolates with decreased susceptibility to azithromycin in 2016 in California compared with prior years. Although there has never been a documented treatment failure to the recommended therapy of CRO and AZI in California, clinicians should remain vigilant for treatment failures given these concerning increases. Disclosures: All authors: No reported disclosures.